Engaging Children with Autism at Historic Sites: Developing an Audience-appropriate Curriculum. (2nd July 2016) - Lurio, Ansel
ABSTRACT: While historic house museums have traditionally employed verbal-based programming, children with autism spectrum disorder (ASD) often feel most comfortable engaged in sensory learning. Historic house museums, due to their tangibility, have the potential to tap into sensory experiences that can teach history to this audience. Despite this advantage, few house museums offer such programming. With an estimated one in 68 students in America diagnosed with ASD [Autism Speaks. 2012. "What is Autism?" Autism Speaks. May 31. Accessed February 4, 2016.https://www.autismspeaks.org/what-autism ] and the need to welcome new audiences to historic houses, this is a key area of work to be explored. The Historic House Trust of New York City is working to become more accessible to children, ages 2–18, with ASD. The author describes the evidence-based curriculum that the Trust is formulating, which can be used as a model of best practices for historic houses to engage such students.